Serious games and One Health in eastern and southern Africa - Gelan, Eyob; Berhe, Tsega; Ayral, Florence; Bourgarel, M.; Conan, A.; Le Page, C.; Lury, Antoine; Maquet, C.; Squarzoni, C.; Tostes, I.; Wairagala, Pamela; Yussuf, Buke; et al. (International Livestock Research Institute, 2025)
The workshop was held on 14–17 October 2025 at the International Livestock Research Institute Addis Ababa campus, bringing together 60 participants from 12 African countries representing government agencies, academia, and the One Health Quadripartite, and facilitators from international organizations.